EFL TEACHERS CHALLENGES AND STRATEGIES OF ONLINE LEARNING IN INDONESIA - Rina Miftachul Ajizah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
This article aims to knowing what challenges faced by high school EFL teachers in online teaching and learning during COVID-19 Pandemic in Indonesia. Then, this article also aims to knowing how they overcome the challenges in that situation. The research design of this study is qualitative research in the descriptive method. The subject of this study is high school EFL teachers, a total of 34 teachers from East Java, and Central Java participated in the online questionnaire. The questionnaire consists of 30 items with a 5-point Likert scale from strongly agree to strongly agree. Then, a total of seven high school EFL teachers participated in online focus group discussion (FGD) as the second instrument of data collection. This instrument is used to strengthen the results of the online questionnaire. The finding of this study is that high school EFL teachers in some regions of Indonesia have challenges in conducting the online teaching and learning during that situation, and they have strategies to overcome the situation of online teaching and learning during the COVID-19 Pandemic in Indonesia. Key words: EFL Teachers, Challenges, Strategies, Online Learning